INTEGRATING ISLAMIC VALUES AND LOCAL ROLE MODELS: A KETOKOHAN-BASED MULTICULTURAL EDUCATION MODEL - Irhamuddin Irhamuddin (Al-Iqro', 2026)
The increasing cultural, ethnic, and religious diversity within contemporary societies has intensified the demand for educational models capable of fostering social cohesion while preserving cultural identities. Although multicultural education has become a significant discourse in educational studies, existing models predominantly emphasize curriculum reform, tolerance, and diversity awareness, with limited attention to the strategic role of local religious role models in internalizing multicultural values. This study aims to develop a Ketokohan-Based Multicultural Education Model by integrating Islamic values with exemplary local leadership to strengthen multicultural competence and social intelligence within Indonesian Muslim communities. This research employs qualitative library research using a conceptual framework approach. Data were collected from scholarly books, peer-reviewed journal articles, and authoritative documents published between 2018 and 2026. The analysis utilized content analysis, comparative analysis, and conceptual synthesis to construct an integrative educational model. The findings demonstrate that Islamic values such as justice ('adl), mercy (rahmah), consultation (shura), tolerance (tasamuh), and moderation (wasatiyyah) become more effectively internalized when transmitted through respected local religious figures who function as educators, mediators, and cultural leaders. The proposed model consists of six interconnected dimensions: Islamic values, local role models, dialogical internalization, multicultural competence, social intelligence, and social harmony. This framework contributes theoretically by extending multicultural education beyond classroom pedagogy toward community-based character formation and offers practical implications for Islamic educational institutions seeking to strengthen inclusive citizenship in pluralistic societies.